Parathyroid hormone and the regulation of cell cycle in colon adenocarcinoma cells - Calvo, Natalia Graciela (2011)
Parathyroid hormone (PTH) functions as a major mediator of bone remodeling and as an essential regulator of calcium homeostasis. In this study, we investigated the role of PTH in the regulation of the cell cycle in human colon adenocarcinoma Caco-2 cells. Flow cytometry analysis revealed that PTH (10-8 M, 12-24 h) treatment increases the number of cells in the G0/G1 phase and diminishes the number in both phases S and G2/M. In addition, analysis by western blot showed that the hormone increases the expression of the inhibitory protein p27Kip1 and diminishes the expression of cyclin D1, cyclin D3 and CDK6. However, the amount of CDK4, p21Cip1, p15INK4B and p16INK4A were not different in the absence or presence of PTH. Inhibitors of PKC (Ro-318220, bisindolylmaleimide and chelerythine), but not JNK (SP600125) and PP2A (okadaic acid and calyculin A), reversed PTH response in Caco-2 cells. Taken together, our results suggest that PTH induces G0/G1 phase arrest of Caco-2 intestinal cells and changes the expression of proteins involved in cell cycle regulation via the PKC signaling pathway.